2013
DOI: 10.1007/s11103-013-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

The rice OsDIL gene plays a role in drought tolerance at vegetative and reproductive stages

Abstract: Drought is one of the critical factors limiting reproductive yields of rice and other crops globally. However, little is known about the molecular mechanism underlying reproductive development under drought stress in rice. To explore the potential gene function for improving rice reproductive development under drought, a drought induced gene, Oryza sativa Drought-Induced LTP (OsDIL) encoding a lipid transfer protein, was identified from our microarray data and selected for further study. OsDIL was primarily ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 59 publications
1
70
0
1
Order By: Relevance
“…In Arabidopsis , the loss-of-function mutant of LTP3 was sensitive to drought stress, whereas overexpressing plants appeared drought tolerant [185]. Moreover, the OsDIL -overexpressing transgenic O. sativa plants were more tolerant to drought stress during vegetative and reproductive development [186]. All these demonstrated that LTP was involved in plant tolerance to drought stress, and is probably a candidate gene for genetic improvement of crop yield in adaption to drought stress.…”
Section: Membrane Traffickingmentioning
confidence: 99%
“…In Arabidopsis , the loss-of-function mutant of LTP3 was sensitive to drought stress, whereas overexpressing plants appeared drought tolerant [185]. Moreover, the OsDIL -overexpressing transgenic O. sativa plants were more tolerant to drought stress during vegetative and reproductive development [186]. All these demonstrated that LTP was involved in plant tolerance to drought stress, and is probably a candidate gene for genetic improvement of crop yield in adaption to drought stress.…”
Section: Membrane Traffickingmentioning
confidence: 99%
“…OsC6 putatively transferred lipid precursors from the tapetum to the anther locule, playing a key role in sporopollenin formation in rice [24]. OsDIL of rice might transfer lipid molecules to synthesize cuticle in leaves to reduce water loss under drought and to facilitate sufficient pollen exine synthesis for microspores against drought [22].…”
Section: Osltpl36 Might Be a Lipid Transporter During Seed Developmenmentioning
confidence: 99%
“…So far, a few nsLTPs of rice have been identified. OsDIL over-expressing transgenic rice plants were more tolerant to drought stress during vegetative development and showed less severe tapetal defects and fewer defective anther sacs when treated with drought at the reproductive stage [22]. OsLTP6 was anther specific expressed through a combination of positive and negative regulatory elements in the promoter region [23].…”
Section: Introductionmentioning
confidence: 99%
“…The locations of the LTPs are varied. LTPs occur in the plasma membrane (Debono et al, 2009; Kim et al, 2012), cell wall (Thoma et al, 1993), or cytoplasm (Guo et al, 2013; Edstam et al, 2014). LTPs are reported to probable participated in cutin synthesis (Pyee et al, 1994; Han et al, 2001; Debono et al, 2009; Kim et al, 2012), pathogen defense responses (Maldonado et al, 2002; Silverstein et al, 2007; Guo et al, 2013; Yu et al, 2013), reproductive development (Chae et al, 2009; Zhang D. et al, 2010; Zhang Y. et al, 2010), and adaption to abiotic stresses (Guo et al, 2013; Pitzschke et al, 2014), even though their functions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As functional proteins, several LTPs are regulated by upstream proteins, like TFs or kinases/phosphatases. In Arabidopsis , LTP3 is positively regulated by MYB96 through direct binding to the LTP3 promoter, and it is involved in plant tolerance levels to freezing and drought stress (Guo et al, 2013). AZI1, a LTP-related hybrid proline-rich protein, and a novel target of mitogen-activated protein kinase 3, is positively regulated by the latter, and plays a role in salt tolerance in plants (Pitzschke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%